Clinical study on leflunomide combined with valsartan in the treatment of diabetic nephropathy proteinuria - WANG Li; ZHANG Jia-gang; LI Yu-ying (Linchuang shenzangbing zazhi)
Objective To investigate the clinical efficacy of leflunomide combined with valsartan in the treatment of diabetic nephropathy(DN) proteinuria.Methods 142 selected DN patients treated in the hospital from July 2013 to July 2015 were divided into two groups by registration order:odd numbers were included into control group and even numbers into research group.The patients in control group(n = 71) took valsartan,and those in research group(n = 71) were given leflunomide combined with valsartan.All the patients were treated with 3 courses and given 6-month follow-up after courses.The 24-h urinary protein quantity,serum albumin(AlB),hypersensitive C-reactive protein(hs-CRP),interleukin-6(IL-6),changes of related indexes of liver and renal function in the two groups before and after treatment were compared.The clinical efficacy and safety of two groups were evaluated.Results As compared with pre-treatment,the 24-h urinary protein quantity,hs-CRP,and IL-6 levels in the two groups were significantly decreased after treatment,while AlB levels,and scores of physical health,mental health,physical activity,and social relations were significantly increased.The above-mentioned indexes in the research group were significantly better than those in the control group(P<0.05).Before and after treatment,there were no obvious changes in alanine transaminase,aspartate aminotransferase,blood urea nitrogen and serum creatinine levels between the two groups,and there were no obvious changes in the group before and after treatment(P>0.05).The total clinical effective rate in research group was 95.77%(68/71),significantly higher than 83.10%(59/71)of control group(P<0.05).Conclusions Leflunomide combined with valsartan for treating proteinuria in DN patients can significantly increase clinical efficacy,relieve clinical symptoms,promote patients recovery,improve survival quality and have no significant influence on liver and renal function,which is a kind of safe and effective treatment method and worthy of further generalization and application.